Zn–Al layered double hydroxides intercalated with carbonate, nitrate, chloride and sulphate ions: Synthesis, characterisation and dye removal properties. Issue 1 (1st January 2017) - Mahjoubi, Fatima Zahra; Khalidi, Abderrahim; Abdennouri, Mohamed; Barka, Noureddine
Abstract: In this work, Zn–Al layered double hydroxides intercalated with carbonate, nitrate, chloride and sulphate ions were synthesised via a co-precipitation method at a constant solution pH. The as-synthesised samples were characterised by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and simultaneous thermogravimetric/differential thermal analysis (TGA-DTA). The XRD patterns showed that Zn-Al-SO4 had the greatest interlayer spacing, followed by Zn-Al-Cl, Zn-Al-NO3 and Zn-Al-CO3 . The FTIR spectra clearly confirmed the presence of intercalated anions in the structure of the LDHs. Batch experiments for methyl orange (MO) adsorption onto synthesised samples were investigated under various conditions such as contact time, initial dye concentration and solution pH. The experimental results show that pH is the most influencing factor. The effective pH range for the MO removal was found to be 3.5–4.5. The kinetics data can be described accurately by a pseudo-second-order kinetic model instead of a pseudo-first-order model. The equilibrium data were analysed using the Langmuir, Freundlich and Dubinin–Radushkevich models. The results showed that the Langmuir and Dubinin–Radushkevich isotherm models fit well to the experimental data. The Zn-Al-LDH samples exhibited exceptional Langmuir maximum adsorption capacities of 2758, 2455, 2270 and 1684 mg/g for Zn-Al-SO4, Zn-Al-Cl, Zn-Al-NO3 and Zn-Al-CO3, respectively.